Porphyromonas gingivalis Evades Immune Clearance by Regulating Lysosome Efflux. (May 2023) - Liu, M.; Shao, J.; Zhao, Y.; Ma, B.; Ge, S.
Porphyromonas gingivalis, a major periodontal pathogen, invades autophagosomes of cells, including gingival epithelial cells, endothelial cells, gingival fibroblasts, macrophages, and dendritic cells, to escape antimicrobial autophagy and lysosome fusion. However, it is not known how P. gingivalis resists autophagic immunity, survives within cells, and induces inflammation. Thus, we investigated whether P. gingivalis could escape antimicrobial autophagy by promoting lysosome efflux to block autophagic maturation, leading to intracellular survival, and whether the growth of P. gingivalis within cells results in cellular oxidative stress, causing mitochondrial damage and inflammatory responses. P. gingivalis invaded human immortalized oral epithelial cells in vitro and mouse oral epithelial cells of gingival tissues in vivo. The production of reactive oxygen species (ROS) increased upon bacterial invasion, as well as mitochondrial dysfunction-related parameters with downregulated mitochondrial membrane potential and intracellular adenosine triphosphate (ATP), upregulated mitochondrial membrane permeability, intracellular Ca 2+ influx, mitochondrial DNA expression, and extracellular ATP. Lysosome excretion was elevated, the number of intracellular lysosomes was diminished, and lysosomal-associated membrane protein 2 was downregulated. Expression of autophagy-related proteins, microtubule-associated protein light chain 3, sequestosome-1, the NLRP3 inflammasome, and interleukin-1β increased with P. gingivalis infection. P. gingivalis may survive in vivo by promoting lysosome efflux, blocking autophagosome-lysosome fusion, and destroying autophagic flux. As a result, ROS and damaged mitochondria accumulated and activated the NLRP3 inflammasome, which recruited the adaptor protein ASC and caspase 1, leading to the production of proinflammatory factor interleukin-1β and inflammation.